PS 08-33 INFLUENCE OF CHANGES IN SERUM URIC ACID LEVELS ON RENAL FUNCTION IN ELDERLY PATIENTS WITH HYPERTENSION: A RETROSPECTIVE COHORT STUDY WITH 3.5-YEAR FOLLOW-UP. (September 2016) - Yu, Peng; Lin, Chunjin; Lin, Fan; Zhang, Hailin; Huang, Feng; Chen, Hui; Zhu, Pengli
Abstract : Objective: Hyperuricemia is closely related to renal diseases. Therefore, the aim of this study was to explore the relationship between the longitudinal changes in serum uric acid and the estimated glomerular filtration rate (eGFR) in a cohort of elderly hypertensive patients. Design and Method: Eighty hundred and thirty-seven re-hospitalized patients with hypertension were included in this retrospective cohort study. Multiple regression analysis was used to investigate the relationship between changes in serum uric acid and renal function after 3.5 years follow-up. Results: The average age at baseline was 69.0+/-10.0 years, and the average follow-up duration was 3.5 years. Multiple linear regression analysis showed that the baseline uric acid levels had a linearly negative correlation with baseline eGFR ( P < 0.01), after adjustment for age, gender, blood pressure, and body mass index, et al. An increase of 100 μmol/L baseline uric acid level resulted in a decrease of 5.684 ml/min/1.73 m 2 in eGFR [95% confidence interval (CI): 7.735–3.633]. Patients with increased uric acid levels had higher risk of renal function decline over the follow-up period, with an adjusted odds ratio of 1.639 (95% CI: 1.129–2.378, P = 0.009), whereas eGFR was remained unchanged in patients with hyperuricemia at baseline and with normal uric acid level 3.5-year later. Conclusions: Longitudinal changes in uric acid levels were independently associated with the renal function decline in elderly patients with hypertension. Uric acid level should be considered in hypertension management in the elderly.